CESifo World Economic Survey May 2015 - Johanna Garnitz; Gernot Nerb; Klaus Wohlrabe; Steffen Henzel (CESifo World Economic Survey, 2015)
World Economic Climate: World Economic Climate continues to brighten - Economic Expectations: Economic expectations slightly more positive - Inflation: Low inflation expectations, particularly in Europe - Currencies: US Dollar seen as overvalued, but expected to rise further - Interest Rates: Divergent development in interest rates expected - Spec ial Topic: Impact of oil price decline on world economy
Keywords: 330